Impact Of Social - Media On The Lifestyle Of Youths In Nepal - Ballav Niroula; Jitendra Prasad Upadhaya (STIE Amkop Makassar, 2023)
Social media is one of the worldwide networking platforms that help as an intermediate for people to join and interconnect with each other. Social media has been widely used by youth to discover new ideas and phenomena around them. This research aims to examine the impact of social media on the lifestyle of youths in Nepal. A descriptive and exploratory research design has been applied to the research. The population of this study is all the youths using social media in the recent period. The research is based on the collected information from 408 youth respondents in Nepal. Primary data were collected from the respondent through a structured survey questionnaire. Data have been analyzed using statistical tools. The findings of the study show that the different types of social media users and the accessibility of media have a positive correlation with the lifestyle of the youth. The impact analysis result of the study is a positive and significant impact on youth’s lifestyle. In addition, the result also showed psychology of users of social media harms the lifestyle of the youth